An Ayurveda Approach in the Management of Central Serous Chorioretinopathy - A Case Study - Panigrahi, Meera; Naveen B S; Ajoy Viswam; Krishnan Namboodiri G (International Journal of Ayurveda and Pharma Research, 2021)
Central Serous Chorioretinopathy (CSC) is one among the retinal disorder and a condition having high recurrence rate relatively; etiology and pathogenesis of which remains indeterminate. The effects on the retina are usually self-limited, although some people are left with permanent vision loss due to progressive and irreversible photoreceptor damage or retinal pigment epithelium atrophy. There have been a number of interventions used in CSC, including laser treatment, photodynamic therapy (PDT), intravitreal injection of anti-vascular endothelial growth factor agents, and sub threshold lasers. In Ayurveda the signs and symptoms of this can be considered under 1st and 2nd Patalagata Timira which described under Dristi gata Roga in all classics of Ayurveda. Pathogenesis suggests involvement of Pitta and Kapha dosha mainly. Therefore a treatment attempt was planned in the lines of Pitta Kapha shamana. After the treatment the quality of vision had been showed significant improvement. Foveal thickness and macular volume in OCT findings also showed significant reduction. The present paper discusses a case study of CSC and its Ayurveda Treatment.